Spirobranchus bakau sp. nov. from Singapore: yet another species of S. kraussii-complex (Polychaeta: Serpulidae) - Sivananthan, Gayathiri D/O; Shantti, Pavarne; Kupriyanova, Elena K.; Quek, Zheng Bin Randolph; Yap, Nicholas Wei Liang; Teo, Serena Lay Ming (Zootaxa, 2021)
The intertidal serpulid polychaete Spirobranchus kraussii was originally described from South Africa and has since been reported in numerous sub (tropical) localities around the world. Recently, however, S. kraussii was uncovered as a complex of morphologically similar and geographically restricted species, raising the need to revise S. cf. kraussii populations. We formally describe S. cf. kraussii from Singapore mangroves as Spirobranchus bakau sp. nov. based on morphological and molecular data. Despite their morphological similarities, Maximum Likelihood and Bayesian Inference analyses of 18S and Cyt b DNA sequence data confirm that S. bakau sp. nov. is genetically distinct from S. kraussii and other known species in the complex. Both analyses recovered S. bakau sp. nov. as part of a strongly supported clade (96% bootstrap, 1 posterior probability), comprising S. sinuspersicus, S. kraussii and S. cf. kraussii from Australia and Hawaii. Additionally, paratypes of S. kraussii var. manilensis, described from Manila Bay in the Philippines, were examined and elevated to the full species S. manilensis. Finally, we tested the hypothesis that fertilisation and embryonic development of S. bakau sp. nov. can occur under the wide range of salinities (19.6–30.9 psu) and temperatures (25–31°C) reported in the Johor Strait. Fertilisation success of ≥70% was achieved across a temperature range of 25–32°C and a salinity range of 20–32 psu. Embryonic development, however, had a narrower salinity tolerance range of 27–32 psu. Clarifying the taxonomic status of S. cf. kraussii populations reported from localities elsewhere in Singapore and Southeast Asia will be useful in establishing the geographical distribution of S. bakau sp. nov. and other members of the S. kraussii-complex.